The effect of Covid-19 lockdown on airborne particulate matter in Rome, Italy: A magnetic point of view. (15th December 2021) - Winkler, Aldo; Amoroso, Antonio; Di Giosa, Alessandro; Marchegiani, Giada
Abstract: Between 9 March and 18 May 2020, strict lockdown measures were adopted in Italy for containing the COVID-19 pandemic: in Rome, despite vehicular traffic on average was more than halved, it was not observed a evident decrease of the airborne particulate matter (PM) concentrations, as assessed by air quality data. In this study, daily PM10 filters were collected from selected automated stations operated in Rome by the regional network of air quality monitoring: their magnetic properties – including magnetic susceptibility, hysteresis parameters and FORC (first order reversal curves) diagrams - were compared during and after the lockdown, for outlining the impact of the COVID-19 measures on airborne particulate matter. In urban traffic sites, the PM10 concentrations did not significantly change after the end of the lockdown, when vehicular traffic promptly returned to its usual levels; conversely, the average volume and mass magnetic susceptibilities approximately doubled, and the linear correlation between volume magnetic susceptibility and PM10 concentration became significant, pointing out the link between PM10 concentrations and the increasing levels of traffic-related magnetic emissions. Magnetite-like minerals, attributed to non-exhaust brakes emissions, dominated the magnetic fraction of PM10 near urban traffic sites, with natural magnetic components emerging in background sites and during exogenous dusts atmospheric events. Magnetic susceptibility constituted a fast and sensitive proxy of vehicular particulate emissions: the magnetic properties can play a relevant role in the source apportionment of PM10, especially when unsignificant variations in its concentration levels may mask important changes in the traffic-related magnetic fraction. As a further hint, increasing attention should be drawn to the reduction of brake wear emissions, that are overcoming by far fuel exhausts as the main particulate pollutant in traffic contexts. Highlights: PM10 concentrations did not increase after the Covid-19 lockdown in Rome. In traffic sites, the mean magnetic susceptibility of PM10 filters doubled after the lockdown. The correlation between PM10 and magnetic susceptibility changed after the lockdown. Non-exhaust brakes emissions dominated the magnetic fraction of PM10 in traffic sites. Magnetic analyses unmasked the increasing levels of vehicular emissions after the lockdown.